Evaluation of prognostic factors on survival in patients with lymph node negative gastric cancer: Three centers experience [Lenf nodu negatif mide kanserli hastalarda saǧkalim üzerine etkili prognostik faktörlerin deǧerlendirilmesi: Üç merkez deneyimi] - (:unkn) unknown (My University, 2010)
OBJECTIVES: In our study, prognostic factors associated with overall survival (OS) and disease-free survival (DFS) in patients without lymph node metastasis after curative surgery, were investigated. METHODS: A total of 113 gastric cancer patients with lymph node negative who had undergone curative gastrectomy, between 2003 and 2010, were retrospectively analyzed. RESULTS: In the univariate analysis pT stage (p<0.001), clinical stage (p<0.001), blood vessel invasion (p=0.033) and recurrence (p<0.001) were found to be an important prognostic factors for OS, while pT stage (p=0.004), clinical stage (p=0.001), blood vessel invasion (p=0.016) and lymphatic vessel invasion (p=0.031) were important prognostic indicators for DFS. Multivariate analysis indicated that pT stage, clinical stage, histological grade and recurrence were independent prognostic factors for OS. Moreover, when multivariate analysis was performed for DFS, surgery type, tumor size, pT stage and clinical stage were found to be independent prognostic indicators. CONCLUSION: Patients with lymph node negative gastric cancer have a high curability and survival compared with cases with lymph node metastasis. © 2010 Onkoloji Derneǧi - © 2010 Association of Oncology.
Keywords: Disease-free survival; Gastric cancer; Lymph node negative tumors; Overall survival